THE INFLUENCE OF THE RENAISSANCE ON ENGLISH LITERATURE - Tagayeva Umida Ernazarovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the profound impact of the Renaissance on English literature, highlighting key literary figures, movements, and themes that emerged during this transformative period. It examines how Renaissance ideals of humanism, classical learning, and individualism influenced literary expression, fostering a rich cultural environment that reshaped English literature. Through an analysis of prominent works and authors, the article aims to illustrate the lasting legacy of the Renaissance in the evolution of English literary traditions.